IMPLEMENTASI KURIKULUM CAMBRIDGE DAN KURIKULUM NASIONAL DI SMA FITRAH ISLAMIC WORLD ACADEMY TAHUN PELAJARAN 2024/2025 - Nizam, Syahrul; Supangat, Supangat; Al Mufti, Muflihin (UNISAN JURNAL, 2025)
This study aims to describe and analyze: (1) how the Cambridge and National curriculum are implemented at SMA Fitrah Islamic World Academy in the 2024/2025 academic year. This research employs a qualitative descriptive approach and was conducted at SMA Fitrah Islamic World Academy from October 2024 to March 2025. The subject of the study is the Head of the Curriculum Division at SMA Fitrah Islamic World Academy, while the informants include the school principal, several Cambridge class teachers, and the Exam Officer Coordinator. Data collection techniques include observation, interviews, and documentation. Data validity techniques involve data triangulation and method triangulation. Data analysis uses an interactive analysis model. The results show that (1) the implementation of the integrated Cambridge and National curriculum includes: (a) planning, which involves preparing human resources, curriculum documents such as RPP (Lesson Plans), syllabi, lesson plans, as well as supporting facilities and learning resources to ensure successful implementation planning; (b) the delivery of learning materials within the integrated curriculum; and (c) evaluation of student learning outcomes through Mid-Semester Assessments (PTS) and Final Semester Assessments (PAS). The advantages of this integrated curriculum are that students receive an international-standard education that aligns with the national curriculum, which helps shape critical and creative thinking skills. Moreover, students have the opportunity to continue their studies abroad through the Cambridge curriculum, supported by Cambridge certification as an entry requirement. However, one of the main challenges lies in language adaptation. The integration requires additional effort in language mastery, making it necessary to have teachers who can teach in English and students who have a sufficient understanding of English to comprehend the material effectively.